Market concentration and pricing behavior in the fertilizer industry: A global approach - Hernandez, Manuel A.; Torero, Máximo (Wiley, 2013)
The global fertilizer industry is a market with high and increasing levels of concentration and trade. Low‐income regions such as sub‐Saharan Africa are highly dependent on imported fertilizer, and the landed price of imports at the port of entry usually represents a large fraction of the fertilizer supply costs in these regions. This article formally examines the relationship between market concentration and prices from a global perspective. We follow a dynamic panel approach using annual data on urea for a panel of countries and observe that prices are generally higher in more concentrated markets using different measures of concentration and model specifications. Based on additional simulations, we find that a 10% increase in competition could increase fertilizer use by 13–19% and rural incomes by 1–2% in regions like sub‐Saharan Africa. Overall, the results highlight the need to further examine the pricing behavior and potential market power exertion of major global producers, which can help to better understand the industry supply chain in developing countries and provide additional insights into the design of policies, including input subsidy programs, intended to promote long‐term fertilizer adoption.